2023
DOI: 10.1177/17456916231180100
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Transient Diversity Is a General Principle for Improving Collective Problem Solving

Abstract: Humans regularly solve complex problems in cooperative teams. A wide range of mechanisms have been identified that improve the quality of solutions achieved by those teams on reaching consensus. We argue that many of these mechanisms work via increasing the transient diversity of solutions while the group attempts to reach a consensus. These mechanisms can operate at the level of individual psychology (e.g., behavioral inertia), interpersonal communication (e.g., transmission noise), or group structure (e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…According to this distribution (and in line with other surveys on climate change opinions [23,72]), the majority of people are somewhat concerned about climate change (with 18% in the 'alarmed' and 33% in the 'concerned' categories), but people appear far from having reached a consensus (with significant fractions of 19% in the 'cautious', 12% in the 'disengaged', 11% in the 'doubtful' and 7% in the 'dismissive' categories in 2008) [43]. In some cases, opinion diversity can be beneficial to collective decision-making, for example, when diversity prevents conformity, groupthink or overconfidence [73,74]. However, as a large body of climate experts judge climate change as a 'threat to human well-being and planetary health' [75] and call for an 'emergency response' [76], continued disagreement among large sectors of the population may undermine the support for policies aiming to produce an adequate response.…”
Section: Discussionmentioning
confidence: 99%
“…According to this distribution (and in line with other surveys on climate change opinions [23,72]), the majority of people are somewhat concerned about climate change (with 18% in the 'alarmed' and 33% in the 'concerned' categories), but people appear far from having reached a consensus (with significant fractions of 19% in the 'cautious', 12% in the 'disengaged', 11% in the 'doubtful' and 7% in the 'dismissive' categories in 2008) [43]. In some cases, opinion diversity can be beneficial to collective decision-making, for example, when diversity prevents conformity, groupthink or overconfidence [73,74]. However, as a large body of climate experts judge climate change as a 'threat to human well-being and planetary health' [75] and call for an 'emergency response' [76], continued disagreement among large sectors of the population may undermine the support for policies aiming to produce an adequate response.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical and theoretical work in cultural evolution has shown that homophilous, heterogeneous social structure, characterized by community structure of the networks on which innovations diffuse, promotes greater cumulative cultural complexity [15][16][17]. Diversity in social structure can support problem-solving [18,19] and prescient ideas often emerge from the peripheries of metapopulations [20]. While homophilous subgroups can promote the development of adaptations and support minority groups, social cohesion can also stifle innovation and lead to conflict [8,21].…”
Section: Introductionmentioning
confidence: 99%
“…An example is the phenomenon of hysteresis (Sznajd-Weron et al, 2024), whereby collective change depends on past collective experiences. Another example are transient states of diversity in collective problem solving (Smaldino et al, 2024).…”
mentioning
confidence: 99%
“…Other articles investigate collective performance and factors that foster or hinder it. Smaldino et al (2024) emphasize the importance of the transient diversity of solutions during collective problem-solving, whereby successful collectives often use a variety of mechanisms to maintain a diverse set of solutions sufficiently long to explore them but not too long to prevent reaching a common solution. Broomell and Davis-Stober (2024) show how a wisdom-of-crowds perspective can be used to understand collective reactions when collectives include influential subgroups that have a biased view of the societal problem at hand.…”
mentioning
confidence: 99%
See 1 more Smart Citation